Network Analysis Reveals the Combination of Controlled-Release and Regular Urea Enhances Microbial Interactions and Improves Maize Yields - Ji, Peng-tao; Du, Xiong; Zhou, Jin-chao; Peng, Yujuan; Li, Xiang-ling; Tao, Pei-jun; Zhang, Yue-chen (Frontiers in Microbiology, 2022)
Increased complexity of microbial networks can contribute to increased biodiversity and multifunctionality and thus crop productivity. However, it is not clear which combination ratio of regular and controlled-release urea will increase the soil microbial community complexity and improve maize yield in the North China Plain. To address this knowledge gap, a two-year field experiment was conducted to explore the effects of the combination of regular (U) and controlled release (S) urea ratios (no fertilizer control (CT), regular urea alone (U), controlled-release urea alone (S), controlled-release urea mixed with regular urea 3:7 (SU3), 5:5 (SU5) and 7:3 (SU7)) on XianYu 688 yield and its rhizosphere and bulk soil microbial community composition and network complexity at different fertility stages. The combination of controlled-release and regular urea increased the N agronomic efficiency, N partial factors productivity, maize yield and grain number per spike, with the maximum maize yield (9186 kg ha-1) being achieved when the ratio of controlled-release urea to regular urea was 3:7 (SU3, p < 0.05). Maize yield increased by 13% in the SU3 treatment compared to the CT treatment. Rhizosphere soil microbial diversity remains stable at the silking stage of maize while increased at the maize physiological maturity stage with the increasing controlled-release to regular N fertilizer ratios (from 3:7 to 7:3, p<0.05). This result suggested that a combination of regular and controlled-release N fertilizer can still substantially increase soil microbial diversity in the later stages of maize growth. The combination of controlled-release and regular urea is more effective in improving microbial network total links and average degree, and N agronomic efficiency (R2=0.79,p<0.01), N partial factors productivity (R2=0.79, p< 0.01), spikes per unit area (R2=0.54, p< 0.05) and maize yield (R2=0.42, p <0.05) increased with the microbial network complexity. This result indicated that the higher microbial network complexity is strongly associated with the higher N agronomic efficiency and N partial factors productivity and maize yield. In conclusion, the ratio of controlled-release to regular urea at SU3 not only increases the yield of maize and N agronomic efficiency but also enhances microbial diversity and network complexity in the North China Plain.